ChemInform Abstract: Benzopyranone, Benzophenone, and Xanthone Derivatives from the Soil Fungus Penicillium citrinum PSU‐RSPG95. Issue 31 (5th August 2014) - Trisuwan, Kongkiat; Rukachaisirikul, Vatcharin; Borwornwiriyapan, Kawitsara; Phongpaichit, Souwalak; Sakayaroj, Jariya
Abstract The two new benzopyranones [coniochaetone E (Ia) and coniochaetone F (Ib)], xanthone [penicillone C (II)], and the new benzophenone [penicillanone (III)] are isolated from the title fungus along with ten known compounds.